Characterization of N Dynamics and Soil Microbial Communities as a Result of Biological Nitrification Inhibition by Brachiaria Grasses - Rivera Zayas, Johanie; Arévalo, Ashly; Trujillo, Catalina; Loaiza, Sandra; Chirinda, Ngonidzashe; Arango, Jacobo; Rice, Charles W. (2017)
Brachiaria spp. are the most widely planted tropical forage with niches from Southeast Asia, Sub-Saharan Africa, Latin American and the Caribbean. This tropical forage grass have a mechanism known as biological nitrification inhibition (BNI) able to inhibit nitrifiers activity. On grazing systems were hotspots of nitrogen (N) concentration from bovine urine deposition generally exceeds plant N uptake rates resulting in environmental losses by leaching and gas emissions the BNI on the Brachiara enhances N utilization in soils, reduces NO3 - leaching and minimizes N2O emissions minimizing the environmental footprint of cattle grazing systems.